Use of linkage to analyze completeness and agreement of deaths from congenital syphilis in the Metropolitan Region of São Paulo, Brazil, 2010-2017: a descriptive study - Almeida, Ana Beatriz Machado de (2021)
Objective: To evaluate the completeness and agreement of infant deaths from congenital syphilis in the Metropolitan Region of Sao Paulo, Brazil, between 2010 and 2017. Methods: Descriptive study based on linkage between Mortality Information System (SIM) and Information System on Live Births (Sinasc). Deaths with mention of congenital syphilis in multiple causes of death were considered. The completeness of 11 SIM variables was analyzed and Sinasc was adopted as reference. Kappa index was used to analyze the agreement. Results: There were 134 deaths by congenital syphilis of which 132 were linked, being 67 as the underlying cause and 65 considering associated causes, indicating underestimation of mortality. After linkage, it increased from two to 10 variables with excellent filling. Conclusion: Linking SIM with Sinasc data improved the completeness. It was identified an underestimation of the magnitude of mortality from congenital syphilis and the use of multiple causes improved its measurement.